Free space optical communication system in the presence of atmospheric losses - Vijayashri V. Belgaonkar; Sundaraguru Ramakrishnan (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
Free space optical communication is gaining importance in the field of optical communication due to its high speed and high bandwidth applications. Free space optical communication system (FSOCS) provides many benefits as compared to traditional wireless communication system and fiber optic cables. This makes this technology the reasonable extension of metropolitan area network and also provides the quick recovery during natural disaster. This system performance is limited due to the atmospheric turbulence effect and various atmospheric losses such as rain, and fog. Gamma gamma atmospheric turbulent model is used to analyze the system performance in the presence of moderate to strong atmospheric turbulence. We have designed the FSO gamma gamma turbulent model with non-return to zero (NRZ) modulation format employing wavelength division multiplexing (WDM), spatial diversity multiple input multiple output (MIMO) (8×8) at various atmospheric turbulence levels and attenuation loss of 10 dB/km at the distance of 2-4 km. Using the proposed model, the link distance is enhanced up to 4km in the presence of turbulence and atmospheric losses with minimum laser transmitted power.